Understanding mechanical behavior of metallic foam with hollow struts using the hollow pentagonal dodecahedron model. (June 2020) - Dai, Rui; Wang, Meng; Wang, Dini; Hu, Zengrong; Green, Matthew D.; Nian, Qiong
Abstract: Nickel (Ni) foam with hollow struts, as one type of ultralight stochastic cellular material, can be simply manufactured by electroplating on a thermally or chemically removable template. A fundamental understanding is required to create a consistent lattice model with capability to capture its mechanical behavior. Herein, an unprecedented hollow pentagonal dodecahedron (HPD) model is proposed with a novel 3D packing architecture. HPD model reveals the scaling of Young's modulus (E) to relative density ( ρ ′) in the factor of 2, which agrees well with uniaxial compression tests. This simplified model paves a way to investigate the cellular material with hollow struts. Graphic abstract: Image, graphical abstract